2010
DOI: 10.2478/v10042-009-0055-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and immunohistochemistry of follicles growth and steroidogenesis in saharian wild sand rat, Psammomys obesus, ovary.

Abstract: Abstract:The sand rat (Psammomys obesus) constitutes a model to study seasonal changes and several metabolic disorders. In order to perform breeding laboratory conditions, the reproductive function of this species living in North Occidental Algerian Sahara was studied. The aim of this work was to investigate the follicular growth changes and the steroidogenic associated aspects. The study was performed using morphometrical and immunohistochemical methods. From primordial to preantral states, the follicle diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Estrogens and progesterone are important in the normal functioning of the female reproductive system. The balance in hormonal interplay between estrogens and progesterone is responsible for a normal regular cycle34,35. Several authors have demonstrated that progesterone secreted during the diestrus phase intensifies the negative feedback of estradiol on basal LH secretion and when the level of progesterone falls at luteal regression, estradiol and LH levels rise and ovulation occurs within the following 6–8 h3639.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens and progesterone are important in the normal functioning of the female reproductive system. The balance in hormonal interplay between estrogens and progesterone is responsible for a normal regular cycle34,35. Several authors have demonstrated that progesterone secreted during the diestrus phase intensifies the negative feedback of estradiol on basal LH secretion and when the level of progesterone falls at luteal regression, estradiol and LH levels rise and ovulation occurs within the following 6–8 h3639.…”
Section: Discussionmentioning
confidence: 99%